2008
DOI: 10.1111/j.1540-8191.2008.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Pericardial Ascending-to-Descending Aortic Bypass Through Median Sternotomy

Abstract: Coarctation of the aorta with concomitant cardiac lesions can be repaired simultaneously through sternotomy and posterior pericardial approach, when patients present in adulthood, to minimize morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…[19] Repair of the aortic coarctation with an ascending-to-descending bypass is safer and easier, particularly in patients with cardiac diseases associated with coarctation or recoarctation. [20][21][22] We performed ascending-to-descending bypass operations in three patients. We monitored the femoral arterial blood pressure during surgery via an arterial line, and we performed ascending aortic and femoral arterial cannulations due to need for perfusion below the coarctation in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Repair of the aortic coarctation with an ascending-to-descending bypass is safer and easier, particularly in patients with cardiac diseases associated with coarctation or recoarctation. [20][21][22] We performed ascending-to-descending bypass operations in three patients. We monitored the femoral arterial blood pressure during surgery via an arterial line, and we performed ascending aortic and femoral arterial cannulations due to need for perfusion below the coarctation in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…As the latter has a problem of long-term graft patency, it may have been appropriate to perform ascending-to-descending aortic bypass in this patient. There are several reports of the outcomes of this operative procedure [12][13][14][15] indicating favorable operative results. However, Pethig, et al 16) reported heart failure and life-threatening ventricular arrhythmias in patients with one-stage aortic valve repair and extra-anatomic bypass grafting for coarctation of the aorta.…”
Section: Discussionmentioning
confidence: 99%